Experimental investigation of the performance of the solar still filled with a hybrid nanofluid - Bellila, Abdelkader (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
This thesis is divided into two parts. Part one: a comparative energy and exergy efficiency study of hemispherical solar still and a single-slope solar still. The overall daily productivity was improved by 47.96% for the hemispherical solar still compared to the single-slope solar still. The maximum daily energy efficiency and exergy efficiency of the single-slope solar still are 25.81 and 1.8%, respectively, and for hemispherical solar still are 38.61 and 3.1%, respectively. The main conclusion from the study is the hemispherical distillery greatly enhances productivity as compared to the single slope distillate and gives more efficiency. Thus, the hemispherical solar still is recommended to be used to provide safe drinking water from salty water. Part two: The hemispherical distiller characteristics are having a large surface area for receiving and condensing compared to a conventional single-slope distiller. To achieve the maximum possible utilization of this feature, in first the Al2O3 nanoparticles were adding to the basin water to increase the evaporation rate, in the second modification the glass cover cooling technology was utilized to increase the condensation rate. To investigate the influences of Al2O3-water nanofluid and the glass cover cooling technology by a water sprinkler on hemispherical solar distiller performance, three hemispherical solar distillers were designed and tested in the same climate conditions. The first is the reference case (conventional hemispherical solar distiller), second is the modified hemispherical solar distiller with Al2O3-water nanofluid, and the third is the modified hemispherical solar distiller with Al2O3-water nanofluid and water sprinkler. Three different concentrations of Al2O3 nanoparticles 0.1, 0.2, and 0.3% were studied. Results showed that, the improvement 41.8, 50.9, and 61.3% of the volume friction of 0.1, 0.2, and 0.3%, respectively. Also, the improvement for utilizing the Al2O3 nanoparticles and water sprinkler reached 105.8, 110.4, and 121% for nanoparticle concentrations 0.1, 0.2, and 0.3%, respectively as compared to the reference case. تنقسم هذه الأطروحة إلى قسمين. القسم الأول: دراسة مقارنة للطاقة وكفاءة الطاقة للمقطرات الشمسية نصف الكروية وأحادية المنحدر. تم تحسين الإنتاجية اليومية الإجمالية بنسبة 47.96 ٪ للمقطرات الشمسية نصف الكروية مقارنةً بالمقطرات الشمسية أحادية المنحدر. الحد الأقصى لكفاءة الطاقة اليومية وكفاءة الطاقة للمقطرات الشمسية أحادية المنحدر هي 25.81 و 1.8٪ على التوالي، وبالنسبة للمقطرات الشمسية نصف الكروية 38.61 و 3.1٪ على التوالي. الاستنتاج الرئيسي من الدراسة هو أن جهاز التقطير النصف كروي يعزز الإنتاجية بشكل كبير بالمقارنة مع نواتج التقطير أحادية المنحدر ويعطي المزيد من الكفاءة. وبالتالي، يوصى باستخدام جهاز التقطير الشمسي النصف كروي لتوفير مياه شرب آمنة من المياه المالحة. الجزء الثاني: تتميز خصائص جهاز التقطير نصف الكروي بمساحة كبيرة للاستقبال والتكثيف مقارنة بجهاز التقطير الشمسي أحادية المنحدر. لتحقيق أقصى استفادة ممكنة من هذه الميزة ، في البداية تم إضافة جزيئات Al2O3 النانوية إلى ماء الحوض لزيادة معدل التبخر، وفي التعديل الثاني تم استخدام تقنية تبريد الغطاء الزجاجي لزيادة معدل التكثيف. للتحقيق في تأثيرات السائل النانوي المائي Al2O3 وتقنية تبريد الغطاء الزجاجي بواسطة رشاش ماء على أداء جهاز التقطير الشمسي نصف كروي، تم تصميم واختبار ثلاثة مقطرات شمسية نصف كروية في نفس الظروف المناخية. الأول هو الحالة المرجعية (المقطر الشمسي التقليدي)، والثاني هو المقطر الشمسي نصف كروي المعدل باستخدام مائع نانوي الماء Al2O3 ، والثالث هو المقطر الشمسي نصف كروي المعدل باستخدام سائل نانوي ماء Al2O3 مع تبريد الغطاء. تمت دراسة ثلاثة تراكيز مختلفة من جزيئات Al2O3 النانوية 0.1 و 0.2 و 0.3٪. أظهرت النتائج أن نسبة التحسن هي 41.8 و 50.9 و 61.3٪ عند استخدام جزيئات Al2O3 النانوية بالتراكيز 0.1 و 0.2 و 0.3٪ على التوالي. كما بلغ التحسن 105.8 و 110.4 و 121٪ عند استخدام تركيزات الجسيمات النانوية 0.1 و 0.2 و 0.3٪ على التوالي، مع تبريد الغطاء، مقارنة بالحالة المرجعية
أطروحة دكتوراه تخصص فيزياء تطبيقية في العلوم الدقيقة
Keywords: Solar energy; Nano- Al2O3; Hemispherical solar distiller; Single-slope solar distiller; Water sprinkler; Constant water flow rate; Distilled water; Productivity.; الطاقة الشمسية؛ نانو-Al2O3؛ المقطر الشمسي النصف كروي؛ المقطر الشمسي أحادي المنحدر؛ تبريد الغطاء الزجاجي؛ معدل تدفق المياه ثابت؛ الماء المقطر؛ الإنتاجية.